INTERPRETASI KONTRADIKTIF ANTARA KOMPETENSI DAN KOMPETISI DALAM KONTEKS SERTIFIKASI GURU - Ketut Bali Sastrawan (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
Teacher certification conducted by LPTK in Indonesia is one of the main problems inthe world of teachers where teachers who have passed the test of a skilled teacher and havefollowed teacher certification training receive a teacher’s compensation allowance of 1 timesthe basic salary each month. Not all teachers can pass the teacher’s ability test because itcalculates the quality of the teacher. Not all teachers who pass the teacher test can be trained inteacher certification well and successfully pass the training. And apparently not all teacherswho have passed teacher certification can get teacher certification benefits. This is becauseevery teacher associated with educators is required to make 24 hours of lessons every week. Ofcourse this will have an impact on the struggle for jam teaching by teachers to fulfill the obligationto be able to undergo the certification allowance. Every teacher teacher continues to increase,while the number of classes each year remains. This has become a problem in itself which is aderivative of the teacher certification program. Each teacher will compete with other teachersto get teaching hours. Whether we realize it or not, the effort to compete with each other isnormal to make teachers as agents of development for education given to the next generation.Keywords: Teacher, Certification, Education